What happens to the learning outcomes of left-behind children when parents are away? Evidence from four pacific island countries - Trang Thu Vu; Daniel Suryadarma (Asian Development Bank Institute (ADBI), 2024)
When parents migrate from home to another place and leave their children behind, it can have a large influence on their children. This study explores the relationship between parental migration and the learning outcomes of left-behind children aged 7-14 in Pacific Island economies, particularly Fiji, Kiribati, Samoa, and Tonga, by using the Multiple Indicator Cluster Survey 6. Using propensity score matching, we observe no significant effects in Fiji, Kiribati, and Tonga. However, our findings indicate that in Samoa, children whose parents are absent from home make significant improvements in their reading skill, despite struggling in mathematics. In addition, living in an extended family could benefit Samoan children when a parent is away. We also find that the effects in Samoa are isolated among girls.
Keywords: I25; I30; F22; 330; Pacific Island countries; left-behind children; foundational skills